2021
DOI: 10.3390/plants10020315
|View full text |Cite
|
Sign up to set email alerts
|

From Genetic Maps to QTL Cloning: An Overview for Durum Wheat

Abstract: Durum wheat is one of the most important cultivated cereal crops, providing nutrients to humans and domestic animals. Durum breeding programs prioritize the improvement of its main agronomic traits; however, the majority of these traits involve complex characteristics with a quantitative inheritance (quantitative trait loci, QTL). This can be solved with the use of genetic maps, new molecular markers, phenotyping data of segregating populations, and increased accessibility to sequences from next-generation seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 217 publications
0
28
0
Order By: Relevance
“…A total of 41QTL studies for quality, abiotic and biotic stress reported inColasuonno et al 11 were analysed, including 36 different traits (Table 1 ). The studies involved 34 different mapping populations, including 53 different parental accessions (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 41QTL studies for quality, abiotic and biotic stress reported inColasuonno et al 11 were analysed, including 36 different traits (Table 1 ). The studies involved 34 different mapping populations, including 53 different parental accessions (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…To correlate between MQTL and previous QTL identified by GWAS, MQTL positions were compared with marker trait associations (MTA) reviewed by Colasuonno et al 11 for abiotic and biotic stress and quality traits. Of the 352 MTA, 58 were located within 33 durum MQTL.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations